Optimal tuning of PI based LF for three-phase SRF PLL synchronization system using pity beetle algorithm under grid abnormalities - P. Riyas; S. A. Lakshmanan (Scientific Reports)
Abstract The importance of grid synchronization in recent years is primarily driven by the widespread integration of renewable energy sources (RES). As nations transition toward carbon–neutral power systems, the variable nature of renewables and the increasing prevalence of non-linear loads introduce significant challenges for maintaining effective grid synchronization. At the core of this process, the synchronous reference frame phase lock loop (SRF PLL) has become a significant component of grid connected power electronic converters (PEC). Generally, PLL includes a proportional integral (PI) based loop filter (LF) that plays a critical role in ensuring precise phase angle and frequency alignment between the grid and PEC. Traditional PI controller tuning techniques like the symmetrical optimum (SO), optimum setting algorithm (OSA) and Ziegler-Nichol’s exhibit satisfactory performance under ideal grid conditions. However, their effectiveness diminishes in real-world scenarios characterized by grid disturbances. To overcome these limitations, this paper proposes a novel PI tuning approach based on the pity beetle algorithm (PBA) for the SRF PLL grid synchronization system. Inspired by the foraging character of the pityogenes chalcographus beetle, PBA optimizes the PI parameters of the LF, enhancing accurate synchronization and response speed. The proposed method is thoroughly assessed under challenging grid abnormalities such as harmonic distortion, amplitude fluctuations, phase jump and unbalanced phase differences. The SRF PLL with proposed PBA tuning for PI based LF is mathematically formulated and analyzed through numerical simulations using MATLAB tool. A comprehensive stability analysis is conducted through frequency response bode plots to validate the effectiveness of the tuning method for accurate grid synchronization. The results, encompassing phase margin (PM), accuracy, computational cost and adaptability derived from the suggested PBA tuned LF design for SRF PLL are compared with existing tuning methods.